Effect of Anaerobic Fermentation on the Aroma Characteristics of Yunnan Arabica Coffee - Chong LU; Xinxin YU; Faguang HU; Xingfei FU; Yuhong ZHAO; Wenjiang DONG (Shipin gongye ke-ji)
In this study, Yunnan Arabica coffee (Coffea arabica L.) was used as raw material, with gas chromatography-mass spectrometry (GC-MS) and electronic nose employed as primary techniques to analyze the transformation of volatile flavor compounds during anaerobic fermentation, followed by the application of multivariate statistical methods to elucidate the evolving patterns of aroma characteristics. The results revealed a decrease in the relative content of furan from 46.88% to 32.5%, an increase in acid content from 8.36% to 10.36%, and an increase in ester content from 6.34% to 15.38%. A total of 42 aromatic compounds were screened by aroma activity value (OAV), with ethyl palmitate, 2-furfural, and acetic acid being the predominant aromatic compounds. Anaerobic fermentation significantly enhanced the flavor characteristics of hazelnut, almond, and floral notes. Benzyl alcohol and 2-pyrrolidone were specific aroma compounds in fermented samples, while 2-acetylpyridine, 2-methyl-5-(1-methylvinyl)pyridine, trans-2-decenal, and propanoic acid are specific aroma compounds in unfermented samples. Anaerobic fermentation time could be manipulated to regulate the aroma characteristics of Yunnan Arabica coffee, where characteristic aromatic compounds could serve as markers for monitoring anaerobic fermentation progress. Different fermentation time had a distinguishable difference on the aroma intensity of 6 kinds of coffee.